Pedagogue’s fallacy and pedagogue’s parsimony - Moulin, Daniel (British Journal of religious education, 2024)
Pedagogue’s fallacy occurs when epistemological principles are applied by educators that in fact do not tell of, or explain, or help understand, the subject at hand. It is identified and introduced in this article to raise an important issue in the construction of pedagogical models of religious education: knowledge is reduced and/or distorted to systematise it for pedagogical purposes. Cases of this fallacy have long been identified in the pages of this journal, albeit implicitly, such as in critiques of the ‘world religions’ approach and debates over other pedagogical models. The purpose of this article is to explore and explicate pedagogue’s fallacy in order to distinguish useful ways to structure and sequence knowledge on the one hand, from erroneous reduction, distortion, or even fabrication on the other. As religious education is diversifying in terms of the disciplines, religious traditions and standpoints with which it engages, understanding and remedying pedagogue’s fallacy has never been more significant. This is because avoiding or mitigating pedagogue’s fallacy is pertinent to achieving and maintaining epistemic justice. I offer the strategy of pedagogue’s parsimony to do this.